An Examination of the Pedagogical Elements Impacting the Classroom Practices of English as a Foreign Language Instructors - Putri, Emiliana (Majapahit Journal of English Studies, 2024)
Pedagogic competence is the ability or skill teachers must possess to recognize the characteristics of their students from various aspects of life, such as moral, emotional, and intellectual. This article analyzes teachers' linguistic ego, views on their teaching role, and attitudes toward English as factors that influence English language teaching and relate to teacher education. This article presents the results of a qualitative research study on pedagogic factors influencing English teaching in three public schools. Three linguistics principles were discussed with five EFL teachers during interviews: interlanguage communication, native language effect, and communicative competence. They all had an undergraduate degree in English and had been teaching English for approximately 3 years. It was concluded that teacher's classroom instructional practice should capitalize on these factors so that teachers can evaluate their teaching skills in the classroom effectively and adapt their methods to ensure high-quality instruction.